A Comparison of US and Canadian Osteoporosis Screening and Treatment Strategies in Postmenopausal Women. (15th January 2019) - Crandall, Carolyn J; Larson, Joseph; Manson, JoAnn E; Cauley, Jane A; LaCroix, Andrea Z; Wactawski‐Wende, Jean; Datta, Mridul; Sattari, Maryam; Schousboe, John T; Leslie, William D; Ensrud, Kristine E
ABSTRACT: The optimal approach to osteoporosis screening and treatment in postmenopausal women is unclear. We compared (i) the United States Preventive Services Task Force (USPSTF) and Osteoporosis Canada osteoporosis screening strategies; and (ii) the National Osteoporosis Foundation (NOF) and Canadian treatment strategies. We used data from the prospective Women's Health Initiative Observational Study and Clinical Trials of women aged 50 to 79 years at baseline ( n  = 117, 707 followed for self‐reported fractures; n  = 8134 in bone mineral density [BMD] subset). We determined the yield of the screening and treatment strategies in identifying women who experienced major osteoporotic fractures (MOFs) during a 10‐year follow‐up. Among women aged 50 to 64 years, 23.1% of women were identified for BMD testing under the USPSTF strategy and 52.3% under the Canadian strategy. For women ≥65 years, 100% were identified for testing under the USPSTF and Canadian strategies, 35% to 74% were identified for treatment under NOF, and 16% to 37% were identified for treatment under CAROC (range among 5‐year age subgroups). Among women who experienced MOF during follow‐up, the USPSTF strategy identified 6.7% of women 50 to 54 years‐old and 49.5% of women 60 to 64 years‐old for BMD testing (versus 54.4% and 60.6% for the Canadian strategy, respectively). However, the specificity of the USPSTF strategy was higher than that of the Canadian strategy among women 50 to 64 years‐old. Among women who experienced MOF during follow‐up, sensitivity for identifying women as treatment candidates was lowest for both strategies in women aged 50 to 64 (NOF 10% to 38%; CAROC 1% to 15%) and maximal in 75‐year‐old to 79‐year‐old women (NOF 82.8%; 51.6% CAROC); specificity declined with advancing age and was lower with the NOF compared to the CAROC strategy. Among women aged 50 to 64 years, the screening and treatment strategies examined had low sensitivity for identifying those who subsequently experience MOF; sensitivity was higher among women ≥65 years than among younger women. New screening and treatment algorithms are needed. © 2018 American Society for Bone and Mineral Research.